PROFIL BERPIKIR RELASIONAL DALAM PEMECAHAN MASALAH MATEMATIKA SISWA SMA DITINJAU DARI GAYA KOGNITIF REFLEKTIF DAN IMPULSIF - Delviera Lukita Wardani (Program Studi S1 Matematika UNESA, 2020)
Relational thinking is one of the interesting problems in mathematics education, this is motivated by the students low relational thinking ability. The characteristic of relational thinking is that students can think by building relationships from various objects/contexts that are related to each other. This type of research is qualitative descriptive research. The analysis of data in this study was done by reducing MFFT test data, troubleshooting tests and interviews, data presentation, and withdrawal conclusions. The subject of this research is two students grade XI of SMA Negeri 15 Surabaya in 2020/2021 year with trigonometric ratio material. In this research, the way students thinking with relationally can be seen from how students build the relationship of information in identifying problems as a whole because there is a possibility of students writing information in full or not also the different concepts they used. Subjects with a reflective cognitive style redrawed the problem to make it easier to solve the problem, while subjects with an impulsive cognitive style only wrote briefly what was known on the problem. The relational way of thinking of reflective cognitive style subjects is more visible than the impulsive cognitive style subjects. One subject mistakenly used the settlement plan. Both of them checking back on the completion of each answer sheet, but the focus of checking is different. Keywords: Cognitive style, Impulsive, Problem solving, Reflective, Relational thinking